The Spatial Planning System and Practice in Post-Socialist Romania: Between the Heritage of “Systematization” and Europenization - Benedek, József (Észak-magyarországi Stratégiai Füzetek, 2023)
This paper offers an overview of the major processes and characteristics of the spatial planning system and practice in Romania. It is largely based on document analysis, proposing an evaluation of the major legislative documents regulating the field of spatial planning (the basic Law nr. 350 from 2001 for Spatial Planning and Urbanism, and additionally, the seven laws composing the National Spatial Planning Act). We focus on the description of the planning practices indetified in the official spatial planning documents from various spatial scales, from regional to local, by considering the interactions established between institutional, economic, political and cultural factors from the socialist period and during the post-socialist transition period. The article argues for the major effects related to a low-speed but obvious Europeanization process of the spatial planning institutions and practices expressed through the uncritical and unreflected introduction of neo-liberal ideas in the spatial planning legislation and practices. The resulting spatial planning system has taken a hybrid shape, represented by a mix of three major European planning styles: comprehensive integrated, land-use oriented and urbanistic planning styles.